Catalytic conversion method for synthesizing methane through hydrogenation of carbon dioxide
By using Al2O3/RuO2/Ag phase materials to adsorb and decompose hydrogen under visible-ultraviolet light irradiation, and synthesize methane with high selectivity in combination with carbon dioxide, the problem of poor selectivity of existing catalysts is solved, and the methane generation rate and selection are significantly improved improves the conversion efficiency of carbon dioxide.
Patent Information
- Application Number
- CN202411624725.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-07
AI Technical Summary
The existing catalysts used for hydrogenation of carbon dioxide to methane have the problem of poor selectivity for methane production, which affects the rapid conversion and recycling efficiency of carbon dioxide.
Al2O3/RuO2/Ag phase material formed by doping three substances: Al2O3, RuO2 and Ag as a catalyst, adsorbs carbon dioxide and hydrogen under visible-ultraviolet light irradiation, decompose hydrogen to form adsorbed hydrogen atoms, and passes a series of reactions Steps to synthesize methane with high selectivity.
The methane generation rate and selectivity were significantly improved, and the methane generation rate increased from 10-12 mmol·gcat-1·h-1 in the conventional method to 16 mmol·gcat-1·h-1, and the selectivity was from 60%-80. % increased to 90%+, improving the conversion efficiency of carbon dioxide.
Smart Images

Figure CN119386858A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon dioxide absorption, conversion, utilization and treatment, and in particular to a catalytic conversion method for synthesizing methane by hydrogenating carbon dioxide. Background Art
[0002] Carbon dioxide is one of the main pollutants emitted by industrial production, building operation and human metabolism. In order to better achieve the goals of carbon peak and carbon neutrality, it is necessary to further develop methods for purifying carbon dioxide by means of adsorption capture, underground storage and other means. In addition, carbon dioxide can also be hydrogenated and catalytically converted into high-value-added chemicals such as methane to achieve multiple recycling of carbon dioxide and achieve the effect of turning waste into treasure.
[0003] CN117599829A has disclosed a method for preparing a catalyst for photothermal carbon dioxide hydrogenation to produce methane; CN116966741A has disclosed an integrated reaction device for carbon dioxide capture and hydrogenation to produce methane; CN116392927A has disclosed an integrated method for capturing and processing carbon dioxide from flue gas emitted by a natural gas boiler; and CN116273119A has disclosed a photothermal catalyst for carbon dioxide reduction and a method for preparing the same. The above patent schemes can all achieve the preparation process of carbon dioxide hydrogenation to methane. However, these existing catalysts for the catalytic conversion of carbon dioxide hydrogenation to methane still have the defect of poor methane production selectivity, which significantly affects the overall efficiency of carbon dioxide hydrogenation catalytic conversion, and it is difficult to meet the needs of rapid conversion / recycling of carbon dioxide.
[0004] Therefore, how to provide a catalytic conversion method that is different from the prior art and can more efficiently realize the catalytic conversion of carbon dioxide to methane has become a problem that needs to be considered and solved by those skilled in the art. Summary of the invention
[0005] In view of the above-mentioned deficiencies of the prior art, the technical problem to be solved by the present invention is: how to provide a catalytic conversion method for synthesizing methane by hydrogenation of carbon dioxide, which is different from the prior art and can more efficiently realize the catalytic conversion synthesis, so as to realize the conversion treatment of carbon dioxide more efficiently.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] A catalytic conversion method for synthesizing methane by hydrogenating carbon dioxide, characterized in that it comprises the following steps:
[0008] In the first step, under the conditions of visible light-ultraviolet light irradiation (light wavelength 320-760 nm), carbon dioxide and hydrogen molecules are adsorbed on the surface of the Al2O3 / RuO2 / Ag phase material to form an adsorbed structure, and hydrogen molecules are decomposed into adsorbed hydrogen atoms; the reaction formula is: CO2 + Al2O3 / RuO2 / Ag → CO2(ad), H2 + Al2O3 / RuO2 / Ag → H2(ad), H2(ad)→ 2 * H(ad);
[0009] In the second step, the adsorbed hydrogen atoms combine with the carbon and oxygen atoms of the adsorbed carbon dioxide molecules to form a HO-CH-OH structure; the reaction formula is: CO2(ad) + 3 * H(ad) → HO-CH-OH(ad);
[0010] The third step is to control the low humidity environment (not higher than RH 0.1%), and the OH and H in the HO-CH-OH structure will remove H2O and form an O-CH structure; the reaction formula is: HO-CH-OH(ad) → O-CH(ad) + H2O;
[0011] Step 4: Under low humidity conditions (not higher than RH 0.1%), the O in the O-CH structure combines with the other two adsorbed hydrogen atoms to remove H2O and form a CH structure; the reaction formula is: O-CH(ad) + 2 * H → CH(ad) + H2O;
[0012] In the fifth step, the CH structure combines with the other three adsorbed hydrogen atoms to generate the methane molecule CH4; the reaction formula is: CH(ad) + 3 * H → CH4(ad).
[0013] Thus, in the present invention, the Al2O3 / RuO2 / Ag phase material formed by the mutual doping of Al2O3, RuO2 and Ag is used as the catalytic conversion synthesis material for synthesizing methane. Through the above reaction process, the catalytic synthesis process of synthesizing carbon dioxide and hydrogen into methane can be completed with high selectivity. Among them, the Al2O3 phase has a large specific surface area (>350 m 2 / g), which can pre-absorb a large amount of carbon dioxide and hydrogen molecules for the subsequent catalytic conversion process; secondly, RuO2 and Ag can be used to promote the decomposition of hydrogen molecules into hydrogen atoms and the combination of carbon dioxide / intermediate reactants with hydrogen atoms, respectively. The synergistic cooperation of the two can effectively improve the overall catalytic conversion rate and improve the selectivity of synthesizing methane.
[0014] Furthermore, the present invention adopts a methane catalytic conversion synthesis material whose main effective component is Al2O3 / RuO2 / Ag phase to realize the catalytic conversion synthesis treatment of carbon dioxide hydrogenation conversion to synthesize methane.
[0015] The specific process principle of the catalytic conversion synthesis treatment is as follows:
[0016] (a) The role of RuO2. RuO2 is a semiconductor with a relatively narrow bandgap. When exposed to visible light, it can cause electrons to jump from the valence band to the conduction band. When hydrogen molecules are adsorbed onto RuO2 or within the action range of RuO2, holes are formed after the valence electrons in RuO2 jump. At this time, the valence electrons in the covalent bonds of the hydrogen molecules are attracted to fill the holes, thereby breaking the covalent bonds and forming adsorbed hydrogen atoms for subsequent hydrogenation of carbon dioxide / intermediate reactants. At the same time, the free electrons formed after the valence electron jump in RuO2 can be used to combine with carbon dioxide or intermediate reactants to form free radical molecules (for example • CO2), strengthens its combination with hydrogen atoms. In addition, the more basic role is that the transition of RuO2 valence electrons under visible light irradiation will trigger the irregular movement of free electrons and hole carriers. This movement process will affect the aluminum and oxygen atoms in the Al2O3 substrate to produce instantaneous dipole moments, strengthen the adsorption of carbon dioxide and hydrogen molecules, and provide a basic force for subsequent hydrogenation and decomposition of hydrogen molecules;
[0017] (b) The role of Ag. As in the basic process of carbon dioxide hydrogenation to methane mentioned above, the carbon and oxygen atoms in carbon dioxide need to form bonds with the adsorbed hydrogen atoms, and the carbon and oxygen atoms themselves cannot provide additional electrons to combine with the valence electrons of hydrogen atoms. Therefore, at this time, in addition to the free electrons formed by the transition of RuO2 valence electrons to migrate to carbon and oxygen atoms as valence electrons, Ag can also directly dissociate and provide the outermost valence electrons. It should be noted that RuO2 will only have a more obvious valence electron transition to form free electrons for carbon dioxide / intermediate reactants under visible light. In weak light or even no light, the ability of RuO2 to produce free electrons will be greatly limited. At this time, Ag can be used as the main component to provide active electrons for carbon dioxide / intermediate reactants to combine with hydrogen atoms to form bonds. Therefore, through the synergistic cooperation of RuO2 and Ag, the Al2O3 / RuO2 / Ag phase can be used for carbon dioxide hydrogenation catalytic conversion in more scenarios.
[0018] Therefore, the present invention can effectively improve the conversion efficiency of carbon dioxide, and improve the generation rate and conversion selectivity of methane. The applicant has verified that the present invention can increase the methane generation rate from 10-12 mmol·g cat -1 ·h -1 Increased to 16 mmol·gcat -1 ·h -1 ; The selectivity of methane generation is increased from 60%-80% in the conventional method to 90%+.
[0019] Furthermore, the methane catalytic conversion synthetic material used in the present invention includes the following phase components in the following mass proportions: 0.1-0.35 parts of Al2O3 phase, 0.05-0.15 parts of RuO2 phase, 0.05-0.20 parts of Ag phase, and 0.30-0.80 parts of Al2O3 / RuO2 / Ag phase.
[0020] Further better mass ratios are: 0.15 parts of Al2O3 phase, 0.10 parts of RuO2 phase, 0.15 parts of Ag phase, and 0.60 parts of Al2O3 / RuO2 / Ag phase.
[0021] Among the above-mentioned methane catalytic conversion synthetic materials, Al2O3 / RuO2 / Ag phase is the main effective component and also the main site of carbon dioxide hydrogenation catalytic conversion reaction, accounting for the largest proportion; at the same time, Al2O3 is used to provide additional adsorption-reaction sites, and RuO2 phase and Ag phase can also assist in enhancing carbon dioxide hydrogenation catalytic conversion reaction and improve conversion efficiency. Moreover, each component is a common reaction product, and its mixing and doping together can play a certain dynamic conversion supplement effect after the main effective component is converted and consumed, so as to better ensure the durability of the treatment effect.
[0022] Furthermore, the methane catalytic conversion synthetic material is prepared by the following steps:
[0023] Step 1: Preparation of porous alumina substrate; weigh 0.5 mol of aluminum nitrate nonahydrate (Al(NO3)3·9H2O) and pour it into 200 ml of deionized water, then pour 0.75 mol of sodium hydroxide (NaOH, analytical grade, 96%) and stir thoroughly; evaporate the mixed suspension and calcine to obtain porous alumina; (As an optimization, after obtaining the mixed suspension, place the mixed suspension in a rotary evaporator, and continue evaporating at 50 °C while continuously bubbling nitrogen (N2) until a solid precipitate is completely obtained; rinse the solid precipitate with deionized water 5 times, then place it in an aluminum crucible, quickly heat it to 500 °C in a muffle furnace and continue calcining in air for 3 h, wherein the heating rate from room temperature to 500 °C is 80 ℃ / min, a white powder / agglomerate is obtained. The above white powder / agglomerate is ground to 200 mesh to obtain porous alumina; this can better ensure the reaction effect and facilitate subsequent preparation)
[0024] Step 2: Loading ruthenium dioxide; 10 g of the porous aluminum oxide prepared above is placed in 200 ml of ethylene glycol solution (C2H6O2, high-grade purity) for stirring and dispersing; (further, during the stirring and dispersing treatment, stirring and mixing is continued at 50 ° C and 200 r / min for 1 hour, and then ultrasonic cleaning is continued for 1 hour; to better ensure the dispersion treatment effect) Then 0.05 mol of ruthenium chloride trihydrate (RuCl3·3H2O) is added to the above aluminum oxide / ethylene glycol mixed suspension, and after the reaction is completed, it is evaporated and dried to obtain agglomerates, which are then ground and calcined to obtain aluminum oxide loaded with ruthenium dioxide (further, the process of evaporation, drying and grinding and calcination is to use a rotary evaporator to evaporate continuously at 80 ° C and 200 r / min for 2 hours; then the rotary evaporation temperature is increased to 150 ° C and the rotary evaporation speed is increased to 500 r / min, and continue evaporating until a completely light black agglomerate is obtained; the light black agglomerate is rinsed 5 times with deionized water and 5 times with acetone (C3H6O, high purity, 99.5%), and then dried in an oven at 80 °C for 48 h. The obtained dried agglomerate is ground to 200 mesh, then placed in an aluminum crucible, and calcined in a muffle furnace at 600 °C / air environment for 5 h. The obtained powder is aluminum oxide loaded with ruthenium dioxide. This better ensures the loading effect)
[0025] Step 3: Loading of elemental silver; pour the aluminum oxide loaded ruthenium dioxide prepared above into 200 ml of deionized water, and stir and disperse (further, the stirring and dispersing process is to continuously stir and mix at 50 ° C and 200 r / min for 1 hour, and to continuously ultrasonically disperse for 1 hour using an ultrasonic cleaning machine to better ensure the dispersion effect and the subsequent reaction effect); add 0.05 mol of silver nitrate (AgNO3) to the above aluminum oxide loaded ruthenium dioxide / deionized water mixed suspension, and then use a rotary evaporator to evaporate, rinse and dry to obtain agglomerates, and then grind and calcine to complete the further loading of elemental silver; (further, after obtaining the mixed suspension, the loading process of elemental silver is completed by using a rotary evaporator to continuously evaporate at 80 ° C and 200 r / min for 2 hours; then the rotary evaporation temperature is increased to 150 ° C and the rotary evaporation speed is increased to 500. r / min, and continue evaporating until a complete precipitate is obtained; the precipitate is rinsed with deionized water for 5 times, and then dried in an oven at 80 °C for 48 h. The obtained dry agglomerate is ground to 200 mesh, then placed in an aluminum crucible, and calcined in a muffle furnace at 600 °C / argon (Ar) for 5 h. The obtained powder is an aluminum oxide-supported ruthenium dioxide / elemental silver composite catalyst. This better ensures the reaction and loading effects).
[0026] The amount of each raw material in the above steps can be adjusted in equal proportions. The chemical reaction characteristics of each step in the above preparation process are as follows:
[0027] In step 1, aluminum nitrate first reacts with sodium hydroxide to form aluminum hydroxide, and then aluminum hydroxide decomposes at high temperature to form aluminum oxide (nitrogen bubbling and rapid temperature decomposition are used to make porous materials to increase the specific surface area of the final product), and the reaction equation is Al(NO3)3 + NaOH → Al(OH)3 + NaNO3, Al(OH)3 → Al2O3 +H2O. In step 2, ruthenium chloride first decomposes at high temperature to form elemental metallic ruthenium, and then elemental ruthenium reacts with oxygen to form ruthenium dioxide (ethylene glycol is used to disperse ruthenium chloride and increase the subsequent ruthenium dioxide generation rate), and the reaction equation is RuCl3 → Ru + Cl2, Ru + O2→ RuO2. In step 3, silver nitrate can be decomposed to form elemental silver under high temperature / argon protection, and the reaction equation is AgNO3 →Ag + NO2 + O2.
[0028] Therefore, the above reaction process can quickly and efficiently produce a catalyst material containing Al2O3 phase, RuO2 phase, Ag phase and Al2O3 / RuO2 / Ag phase. Its main active component is Al2O3 / RuO2 / Ag phase, which ensures the efficient catalytic synthesis effect of carbon dioxide hydrogenation to methane. At the same time, other phases are evenly mixed and doped together, which can play a certain dynamic conversion supplement effect after the main active components are converted and consumed, and the generated independent Al2O3 phase, RuO2 phase and Ag phase also have a certain synthetic conversion effect on carbon dioxide hydrogenation; therefore, the overall selectivity of carbon dioxide hydrogenation to methane can be better improved.
[0029] In summary, the present invention can provide a method for realizing the synthesis of methane by hydrogenation conversion of carbon dioxide, which is different from the prior art, and can realize the conversion treatment of carbon dioxide more efficiently, thereby improving the selectivity of methane synthesis. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the process of hydrogenation of carbon dioxide into methane on the surface of single-layer graphite / In2O3 / MnO2 phase.
[0031] Figure 2 It is a schematic diagram comparing the methane conversion rate of the methane catalytic conversion synthesis material of the present invention and other types of methane synthesis catalyst materials.
[0032] Figure 3 It is a schematic diagram comparing the methane generation selectivity data of the methane catalytic conversion synthesis material of the present invention and other types of methane synthesis catalyst materials. DETAILED DESCRIPTION
[0033] The present invention is further described in detail below in conjunction with specific implementation modes.
[0034] Embodiment: A catalytic conversion method for synthesizing methane by hydrogenating carbon dioxide, characterized in that it comprises the following steps:
[0035] In the first step, under the conditions of visible light-ultraviolet light irradiation (light wavelength 320-760 nm), carbon dioxide and hydrogen molecules are adsorbed on the surface of the Al2O3 / RuO2 / Ag phase material to form an adsorbed structure, and hydrogen molecules are decomposed into adsorbed hydrogen atoms; the reaction formula is: CO2 + Al2O3 / RuO2 / Ag → CO2(ad), H2 + Al2O3 / RuO2 / Ag → H2(ad), H2(ad)→ 2 * H(ad);
[0036] In the second step, the adsorbed hydrogen atoms combine with the carbon and oxygen atoms of the adsorbed carbon dioxide molecules to form a HO-CH-OH structure; the reaction formula is: CO2(ad) + 3 * H(ad) → HO-CH-OH(ad);
[0037] The third step is to control the low humidity environment (not higher than RH 0.1%), and the OH and H in the HO-CH-OH structure will remove H2O and form an O-CH structure; the reaction formula is: HO-CH-OH(ad) → O-CH(ad) + H2O;
[0038] Step 4: Under low humidity conditions (not higher than RH 0.1%), the O in the O-CH structure combines with the other two adsorbed hydrogen atoms to remove H2O and form a CH structure; the reaction formula is: O-CH(ad) + 2 * H → CH(ad) + H2O;
[0039] In the fifth step, the CH structure combines with the other three adsorbed hydrogen atoms to generate the methane molecule CH4; the reaction formula is: CH(ad) + 3 * H → CH4(ad).
[0040] Thus, in the present invention, the Al2O3 / RuO2 / Ag phase material formed by the mutual doping of Al2O3, RuO2 and Ag is used as the catalytic conversion synthesis material for synthesizing methane. Through the above reaction process, the catalytic synthesis process of synthesizing carbon dioxide and hydrogen into methane can be completed with high selectivity. Among them, the Al2O3 phase has a large specific surface area (>350 m 2 / g), which can pre-absorb a large amount of carbon dioxide and hydrogen molecules for the subsequent catalytic conversion process; secondly, RuO2 and Ag can be used to promote the decomposition of hydrogen molecules into hydrogen atoms and the combination of carbon dioxide / intermediate reactants with hydrogen atoms, respectively. The synergistic cooperation of the two can effectively improve the overall catalytic conversion rate and improve the selectivity of synthesizing methane.
[0041] During implementation, the present invention adopts a methane catalytic conversion synthesis material whose main effective component is Al2O3 / RuO2 / Ag phase to realize the catalytic conversion synthesis treatment of carbon dioxide hydrogenation conversion to synthesize methane.
[0042] The specific process principle of the catalytic conversion synthesis treatment is as follows, see Figure 1 :
[0043] (a) The role of RuO2. RuO2 is a semiconductor with a relatively narrow bandgap. When exposed to visible light, it can cause electrons to jump from the valence band to the conduction band. When hydrogen molecules are adsorbed onto RuO2 or within the action range of RuO2, holes are formed after the valence electrons in RuO2 jump. At this time, the valence electrons in the covalent bonds of the hydrogen molecules are attracted to fill the holes, thereby breaking the covalent bonds and forming adsorbed hydrogen atoms for subsequent hydrogenation of carbon dioxide / intermediate reactants. At the same time, the free electrons formed after the valence electron jump in RuO2 can be used to combine with carbon dioxide or intermediate reactants to form free radical molecules (for example • CO2), strengthens its combination with hydrogen atoms. In addition, the more basic role is that the transition of RuO2 valence electrons under visible light irradiation will trigger the irregular movement of free electrons and hole carriers. This movement process will affect the aluminum and oxygen atoms in the Al2O3 substrate to produce instantaneous dipole moments, strengthen the adsorption of carbon dioxide and hydrogen molecules, and provide a basic force for subsequent hydrogenation and decomposition of hydrogen molecules;
[0044] (b) The role of Ag. As in the basic process of carbon dioxide hydrogenation to methane mentioned above, the carbon and oxygen atoms in carbon dioxide need to form bonds with the adsorbed hydrogen atoms, and the carbon and oxygen atoms themselves cannot provide additional electrons to combine with the valence electrons of hydrogen atoms. Therefore, at this time, in addition to the free electrons formed by the transition of RuO2 valence electrons to migrate to carbon and oxygen atoms as valence electrons, Ag can also directly dissociate and provide the outermost valence electrons. It should be noted that RuO2 will only have a more obvious valence electron transition to form free electrons for carbon dioxide / intermediate reactants under visible light. In weak light or even no light, the ability of RuO2 to produce free electrons will be greatly limited. At this time, Ag can be used as the main component to provide active electrons for carbon dioxide / intermediate reactants to combine with hydrogen atoms to form bonds. Therefore, through the synergistic cooperation of RuO2 and Ag, the Al2O3 / RuO2 / Ag phase can be used for carbon dioxide hydrogenation catalytic conversion in more scenarios.
[0045] Therefore, the present invention can effectively improve the conversion efficiency of carbon dioxide, and improve the generation rate and conversion selectivity of methane. The applicant has verified that the present invention can increase the methane generation rate from 10-12 mmol·g cat -1 ·h -1 Increased to 16 mmol·g cat -1 ·h -1 ; The selectivity of methane generation is increased from 60%-80% in the conventional method to 90%+.
[0046] Specifically, the methane catalytic conversion synthetic material used in the present invention includes the following phase components in the following mass proportions: 0.1-0.35 parts of Al2O3 phase, 0.05-0.15 parts of RuO2 phase, 0.05-0.20 parts of Ag phase, and 0.30-0.80 parts of Al2O3 / RuO2 / Ag phase.
[0047] The better mass proportions are: 0.15 parts of Al2O3 phase, 0.10 parts of RuO2 phase, 0.15 parts of Ag phase, and 0.60 parts of Al2O3 / RuO2 / Ag phase.
[0048] Among the above-mentioned methane catalytic conversion synthetic materials, Al2O3 / RuO2 / Ag phase is the main effective component and also the main site of carbon dioxide hydrogenation catalytic conversion reaction, accounting for the largest proportion; at the same time, Al2O3 is used to provide additional adsorption-reaction sites, and RuO2 phase and Ag phase can also assist in enhancing carbon dioxide hydrogenation catalytic conversion reaction and improve conversion efficiency. Moreover, each component is a common reaction product, and its mixing and doping together can play a certain dynamic conversion supplement effect after the main effective component is converted and consumed, so as to better ensure the durability of the treatment effect.
[0049] During implementation, the methane catalytic conversion synthetic material is prepared by the following steps:
[0050] Step 1: Preparation of porous alumina substrate; weigh 0.5 mol of aluminum nitrate nonahydrate (Al(NO3)3·9H2O) and pour it into 200 ml of deionized water, then pour 0.75 mol of sodium hydroxide (NaOH, analytical grade, 96%) and stir thoroughly; place the mixed suspension in a rotary evaporator, and continue evaporating at 50 °C while continuously bubbling nitrogen (N2) until a solid precipitate is completely obtained; rinse the solid precipitate with deionized water 5 times, then place it in an aluminum crucible, quickly heat it to 500 °C in a muffle furnace and continue calcining in an air environment for 3 h, wherein the heating rate from room temperature to 500 °C is 80 °C / min, to obtain a white powder / agglomerate. Grind the above white powder / agglomerate to 200 mesh to obtain porous alumina;
[0051] Step 2: Loading of ruthenium dioxide; 10 g of the porous alumina prepared as above was placed in 200 ml of ethylene glycol solution (C2H6O2, high-grade pure), stirred and mixed continuously at 50 °C and 200 r / min for 1 h, and then subjected to ultrasonic dispersion treatment for 1 h using an ultrasonic cleaner; 0.05 mol of ruthenium chloride trihydrate (RuCl3·3H2O) was then added to the alumina / ethylene glycol mixed suspension, and then evaporated continuously at 80 °C and 200 r / min for 2 h using a rotary evaporator; then the rotary evaporation temperature was increased to 150 °C and the rotary evaporation speed was increased to 500 r / min, and evaporation was continued until a completely light black agglomerate was obtained; the light black agglomerate was rinsed 5 times with deionized water and 5 times with acetone (C3H6O, high-grade pure, 99.5%), and then dried continuously at 80 °C in an oven for 48 h. The obtained dried agglomerate was ground into 200 mesh, and then placed in an aluminum crucible, and calcined in a muffle furnace at 600 °C in air for 5 h. The obtained powder was aluminum oxide loaded with ruthenium dioxide.
[0052] Step 3: Loading of elemental silver; pour the aluminum oxide loaded ruthenium dioxide prepared above into 200 ml of deionized water, stir and mix continuously at 50 °C and 200 r / min for 1 h, and continue ultrasonic dispersion treatment in an ultrasonic cleaner for 1 h; add 0.05 mol of silver nitrate (AgNO3) to the above aluminum oxide loaded ruthenium dioxide / deionized water mixed suspension, and then use a rotary evaporator to evaporate continuously at 80 °C and 200 r / min for 2 h; then increase the rotary evaporation temperature to 150 °C and the rotary evaporation speed to 500 r / min, and continue evaporation until a complete precipitate is obtained; rinse the precipitate with deionized water 5 times, and then dry it in an oven at 80 °C for 48 h. The obtained dried agglomerate was ground into 200 mesh, and then placed in an aluminum crucible, and calcined in a muffle furnace at 600 ° C / argon (Ar) protection for 5 h. The obtained powder was the aluminum oxide-supported ruthenium dioxide / elemental silver composite catalyst.
[0053] The amount of each raw material in the above steps can be adjusted in equal proportions. The chemical reaction characteristics of each step in the above preparation process are as follows:
[0054] In step 1, aluminum nitrate first reacts with sodium hydroxide to form aluminum hydroxide, and then aluminum hydroxide decomposes at high temperature to form aluminum oxide (nitrogen bubbling and rapid temperature decomposition are used to make porous materials to increase the specific surface area of the final product), and the reaction equation is Al(NO3)3 + NaOH → Al(OH)3 + NaNO3, Al(OH)3 → Al2O3 +H2O. In step 2, ruthenium chloride first decomposes at high temperature to form elemental metallic ruthenium, and then elemental ruthenium reacts with oxygen to form ruthenium dioxide (ethylene glycol is used to disperse ruthenium chloride and increase the subsequent ruthenium dioxide generation rate), and the reaction equation is RuCl3 → Ru + Cl2, Ru + O2→ RuO2. In step 3, silver nitrate can be decomposed to form elemental silver under high temperature / argon protection, and the reaction equation is AgNO3 →Ag + NO2 + O2.
[0055] Therefore, the above reaction process can quickly and efficiently produce a catalyst material containing Al2O3 phase, RuO2 phase, Ag phase and Al2O3 / RuO2 / Ag phase. Its main active component is Al2O3 / RuO2 / Ag phase, which ensures the efficient catalytic synthesis effect of carbon dioxide hydrogenation to methane. At the same time, other phases are evenly mixed and doped together, which can play a certain dynamic conversion supplement effect after the main active components are converted and consumed, and the generated independent Al2O3 phase, RuO2 phase and Ag phase also have a certain synthetic conversion effect on carbon dioxide hydrogenation; therefore, the overall selectivity of carbon dioxide hydrogenation to methane can be better improved.
[0056] In order to better verify the effect of the present invention, the applicant conducted a comparative test, using the methane catalytic conversion synthetic material obtained in the above specific embodiment as the experimental group, and other methane catalytic conversion synthetic materials as the comparative group, and conducted conversion rate comparison test and selectivity comparison test respectively. The test results are shown in Figure 2 and Figure 3 .
[0057] for Figure 2 Under the environmental conditions of 250 ℃ / 5 MPa / 0% relative humidity / 320-760 nm light, TiO2-loaded Ni and TiO2 / SAB-15-loaded RuO2 were used as control catalysts, and the molar contents of hydrogen (reaction gas) and nitrogen (carrier gas) were set to 76% and 5%, respectively, to compare the rate of 19% carbon dioxide hydrogenation catalytic conversion to methane. From the experimental results, it can be seen that the methane generation rate of the above control catalysts is lower than that of Al2O3-loaded RuO2 / Ag catalysts, especially the methane generation rate of Al2O3-loaded RuO2 / Ag is much higher than that of TiO2-loaded Ni, indicating that the coexistence of RuO2 and Ag can make the Al2O3 surface catalyze carbon dioxide to have a synergistic effect, greatly enhancing the hydrogenation catalytic conversion ability of this type of composite catalyst.
[0058] for Figure 3 , under the environmental conditions of 250 ℃ / 5 MPa / 0% relative humidity / 320-760 nm light, TiO2-loaded Ni and TiO2 / SAB-15-loaded RuO2 were used as control catalysts, and the molar contents of hydrogen (reaction gas) and nitrogen (carrier gas) were set to 76% and 5%, respectively, to conduct comparative experiments on the selectivity of 19% carbon dioxide hydrogenation catalytic conversion to methane. From the experimental results, it can be seen that the methane generation selectivity of the above control catalysts is lower than that of Al2O3-loaded RuO2 / Ag catalysts, especially the methane generation selectivity of Al2O3-loaded RuO2 / Ag is much higher than that of TiO2-loaded Ni, indicating that the coexistence of RuO2 and Ag can make the Al2O3 surface catalyze carbon dioxide to have a synergistic effect, greatly enhancing the hydrogenation catalytic conversion ability of this type of composite catalyst.
Claims
1. A catalytic conversion method for synthesizing methane by hydrogenating carbon dioxide, characterized in that: The following steps are involved: In the first step, under the conditions of visible light-ultraviolet light irradiation, carbon dioxide and hydrogen molecules are adsorbed on the surface of the Al2O3 / RuO2 / Ag phase material to form an adsorbed structure, and hydrogen molecules are decomposed into adsorbed hydrogen atoms; the reaction formula is: CO2 + Al2O3 / RuO2 / Ag → CO2(ad), H2 + Al2O3 / RuO2 / Ag → H2(ad), H2(ad) → 2 * H(ad); In the second step, the adsorbed hydrogen atoms combine with the carbon and oxygen atoms of the adsorbed carbon dioxide molecules to form a HO-CH-OH structure; the reaction formula is: CO2(ad) + 3 * H(ad) → HO-CH-OH(ad); In the third step, the OH and H in the HO-CH-OH structure are controlled in a low humidity environment not higher than RH 0.1%, and H2O is removed to form an O-CH structure; the reaction formula is: HO-CH-OH(ad) → O-CH(ad) + H2O; The fourth step is to control the humidity in a low humidity environment of no more than RH 0.1%, and the O in the O-CH structure combines with the other two adsorbed hydrogen atoms to remove H2O again and form a CH structure; the reaction formula is: O-CH(ad) + 2 * H → CH(ad) + H2O; In the fifth step, the CH structure combines with the other three adsorbed hydrogen atoms to generate the methane molecule CH4; the reaction formula is: CH(ad) +3 * H → CH4(ad).
2. The catalytic conversion method for synthesizing methane by hydrogenation of carbon dioxide according to claim 1, characterized in that: The method adopts a methane catalytic conversion synthesis material whose main effective component is Al2O3 / RuO2 / Ag phase to realize the catalytic conversion synthesis treatment of carbon dioxide hydrogenation conversion to synthesize methane.
3. The catalytic conversion method for synthesizing methane by hydrogenation of carbon dioxide according to claim 2, characterized in that: The methane catalytic conversion synthetic material used includes the following phase components in the following mass proportions: 0.1-0.35 parts of Al2O3 phase, 0.05-0.15 parts of RuO2 phase, 0.05-0.20 parts of Ag phase, and 0.30-0.80 parts of Al2O3 / RuO2 / Ag phase.
4. The catalytic conversion method for synthesizing methane by hydrogenation of carbon dioxide according to claim 3, characterized in that: The methane catalytic conversion synthetic material used includes the following phase components in the following mass proportions: 0.15 parts of Al2O3 phase, 0.10 parts of RuO2 phase, 0.15 parts of Ag phase, and 0.60 parts of Al2O3 / RuO2 / Ag phase.
5. The catalytic conversion method for synthesizing methane by hydrogenation of carbon dioxide according to claim 3, characterized in that: The methane catalytic conversion synthetic material is prepared by the following steps: Step 1: preparing a porous aluminum oxide substrate; weighing 0.5 mol of aluminum nitrate nonahydrate and pouring it into 200 ml of deionized water, and then pouring 0.75 mol of sodium hydroxide and stirring and mixing thoroughly; evaporating the suspension obtained by mixing and calcining to obtain porous aluminum oxide; Step 2: Loading ruthenium dioxide; taking 10 g of the porous aluminum oxide prepared above and placing it in 200 ml of ethylene glycol solution, stirring and dispersing it; then adding 0.05 mol of ruthenium chloride trihydrate to the aluminum oxide / ethylene glycol mixed suspension, evaporating and drying to obtain agglomerates after the reaction is completed, and then grinding and calcining to obtain aluminum oxide loaded with ruthenium dioxide; Step 3: Loading of elemental silver; pour the above-prepared aluminum oxide loaded ruthenium dioxide into 200 ml of deionized water and stir to disperse; add 0.05 mol of silver nitrate to the above aluminum oxide loaded ruthenium dioxide / deionized water mixed suspension, then evaporate using a rotary evaporator, rinse and dry to obtain agglomerates, and then grind and calcine to complete further loading of elemental silver.
6. The catalytic conversion method for synthesizing methane by hydrogenation of carbon dioxide according to claim 5, characterized in that: In step 1, after obtaining the mixed suspension, the mixed suspension is placed in a rotary evaporator, and evaporated at 50 ° C while continuously bubbling nitrogen until a solid precipitate is completely obtained; the solid precipitate is rinsed 5 times with deionized water, then placed in an aluminum crucible, and quickly heated to 500 ° C in a muffle furnace and continuously calcined for 3 h in an air environment, wherein the heating rate from room temperature to 500 ° C is 80 ° C / min, to obtain a white powder / agglomerate; the above white powder / agglomerate is ground to 200 mesh to obtain porous alumina.
7. The catalytic conversion method for synthesizing methane by hydrogenation of carbon dioxide according to claim 5, characterized in that: In step 2, during the stirring and dispersing treatment, the stirring and mixing is continued at 50° C. and 200 r / min for 1 hour, and then an ultrasonic cleaning machine is used to continuously perform ultrasonic dispersion treatment for 1 hour.
8. The catalytic conversion method for synthesizing methane by hydrogenation of carbon dioxide according to claim 5, characterized in that: In step 2, the process of evaporation, drying, grinding and calcination is to use a rotary evaporator to evaporate continuously at 80 ° C at 200 r / min for 2 h; then increase the rotary evaporation temperature to 150 ° C, the rotary evaporation speed to 500 r / min, and continue evaporation until a completely light black agglomerate is obtained; the light black agglomerate is rinsed with deionized water 5 times and acetone 5 times, and then dried in an oven at 80 ° C for 48 h; the obtained dried agglomerate is ground to 200 mesh, and then placed in an aluminum crucible, and calcined in a muffle furnace at 600 ° C / air environment for 5 h, and the obtained powder is aluminum oxide loaded with ruthenium dioxide.
9. The catalytic conversion method for synthesizing methane by hydrogenation of carbon dioxide according to claim 5, characterized in that: In step 3, the stirring and dispersing process is to continuously stir and mix at 50°C and 200 r / min for 1 hour, and to continuously perform ultrasonic dispersing treatment for 1 hour using an ultrasonic cleaning machine.
10. The catalytic conversion method for synthesizing methane by hydrogenation of carbon dioxide according to claim 5, characterized in that: In step 3, after obtaining the mixed suspension, the loading process of elemental silver is completed by using a rotary evaporator to evaporate continuously at 200 r / min at 80°C for 2 h; then the rotary evaporation temperature is increased to 150°C and the rotary evaporation speed is increased to 500 r / min, and evaporation is continued until a complete precipitate is obtained; the precipitate is rinsed with deionized water 5 times, and then dried in an oven at 80°C for 48 h; the obtained dry agglomerate is ground to 200 mesh, and then placed in an aluminum crucible, and calcined continuously at 600°C / argon protection in a muffle furnace for 5 h. The obtained powder is an alumina-loaded ruthenium dioxide / elemental silver composite catalyst.
Citation Information
Patent Citations
Photo-thermal catalyst for carbon dioxide reduction and preparation method thereof
CN116273119A
Carbon dioxide capturing and processing integrated method for flue gas discharged by natural gas boiler
CN116392927A
Integrated reaction device for producing methane through carbon dioxide trapping and hydrogenation
CN116966741A
Preparation method of photo-thermal carbon dioxide hydrogenation methane preparation catalyst
CN117599829A